EMPOWERMENT OF CREATIVE WOMEN IN VARIOUS SNACKS BUSINESS HOME INDUSTRY BADEAN VILLAGE BLIMBINGSARI DISTRICT BANYUWANGI - Supono; Achmad Zayul Mustain (International Jurnal of Education Schoolars, 2021)
Community Partnership Program (PKM) entitled Women Pemberdayaan Creative In Business Various Snacks Home Industry Badean Village Banyuwangi is carried out with the aim of helping solve problems faced by food business partners made from cowhide as fostered by Home Industries in Badean Village, Blimbingsari District, Banyuwangi Regency. Badean Village which is a community service partner. The problems faced by partners are: 1) sales are still around Blimbingsari District, 2) partners do not understand entrepreneurship management, 3) the legality of product results that have not been registered with the Health Service and halal at MUI and POM Hall, 4) the production process still uses tools simple. In the past, cowhide was only used as a raw material for shoes. Along with the development of industrial technology, cowhide is widely used as snack food in the form of rambak crackers. Cowhide is used as a variety of foods to increase the selling value of cowhide and become a new business area for the local community. Optimization in business management and marketing of local products in Badean Village can be an effort to improve the economy of the Badean Village community. Solutions to problems can be provided based on the results of problem identification that become a reference in preparation, implementation, monitoring, evaluation and reporting. The solutions that can be offered to partners are: 1) business management and marketing training for the cracker rambak business community in Badean Village, 2) assistance in managing product permits at the Health Office, halal at MUI and POM Hall, 3) appropriate technology tools in the form of electrical packaging to meet the quantity and quality of production. The indicators of achievement that are expected from the implementation of community service in Badean Village, namely: increasing community knowledge and skills, increasing the number of processed rambak cracker products produced, increasing the quality of rambak cracker processed products, increasing the income of the Badean village community with the wider marketing area of rambak crackers processed. Home Industry products. So that the processed cracker rambak in Badean Village is not only popular in the Blimbingsari District, but the processed rambak cracker in Badean Village can also be one of the typical Banyuwangi souvenirs that must be sought by local and foreign